Nitrate fusion synthesis and two-step sintering of nanocrystalline yttria stabilized hafnia powders. Issue 7 (May 2018) - Kumar, D. Sanjay; Ananthasivan, K.; Senapati, Abhiram; Amirthapandian, S.; Dasgupta, Arup
Abstract: Bulk quantities of nanocrystalline yttria stabilized hafnia (YSH) powders with crystallite size ranging from 8 to 15 nm were successfully prepared for the first time through nitrate fusion synthesis at a temperature as low as 673 K. The yttrium content was varied from 6 to 30 mol%. The dependence of the properties of the final product on the quantity of the dopant was investigated. Microstructural investigations were carried out with scanning electron microscopy and transmission electron microscopy. A maximum relative sintered density of 98.2 ± 0.3% T.D (theoretical density) was obtained for YSH containing 10 mol% yttrium by using "two-step sintering" at a final temperature of 1773 K. Anisotropic shrinkage factor (0.70–0.95) was found to vary linearly with the compaction pressure. SEM investigations reaffirmed that the sintered pellets comprised uniform distribution of faceted grains and elemental mapping revealed that yttrium is distributed uniformly in these sintered YSH monoliths. Graphical abstract: fx1